Sensitivity Enhancement of a Surface Plasmon Resonance with Tin Selenide (SnSe) Allotropes - Xiaoyu Dai; Yanzhao Liang; Yuting Zhao; Shuaiwen Gan; Yue Jia; Yuanjiang Xiang (Sensors, 2019)
Single layers of tin selenide (SnSe), which have a similar structure as graphene and phosphorene, also show excellent optoelectronic properties, and have received much attention as a two-dimensional (2D) material beyond other 2D material family members. Surface plasmon resonance (SPR) sensors based on three monolayer SnSe allotropes are investigated with the transfer matrix method. The simulated results have indicated that the proposed SnSe-containing biochemical sensors are suitable to detect different types of analytes. Compared with the conventional Ag-only film biochemical sensor whose sensitivity is 116°/RIU, the sensitivities of these SnSe-based biochemical sensors containing α-SnSe, δ-SnSe, ε-SnSe, were obviously increased to 178°/RIU, 156°/RIU and 154°/RIU, respectively. The diverse biosensor sensitivities achieved with these three SnSe allotropes suggest that these 2D materials can adjust SPR sensor properties.